Cinco inscripciones singulares del foro de Segobriga - Alföldy, Géza; Abascal Palazón, Juan Manuel; Cebrián Fernández, Rosario (Anales de prehistoria y arqueologia, 2002)
The excavations at the forum of Segobriga have provided us many Roman inscriptions; we show a srnall serie of honorific titles, belonging to the epigraphical program at this site.
Elektronische Reproduktion der Druckausgabe
Band im PDF-Dokument falsch als 16/17 angegeben
Gesehen am 22.03.2024